Corporate governanace and corporate scandals - Mursalov, Elvin; Králíček, Vladimír, 1952-; Jurka, Robert; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2022)
In its most basic form, corporate governance is an approach to managing businesses with the intention of producing the greatest possible benefits for the shareholders and other stakeholders involved. This approach has become one of the most hotly debated topics in the world of business in recent years. In recent years, there has been a great deal of interest in the topic of corporate governance. This is largely attributable to the fact that good corporate governance clearly contributes to the overall economic well-being of both institutions and society. Furthermore, good corporate governance is a requirement that has become necessary as a result of globalization and the shifting nature of the competitive environment. This diploma thesis has been done on corporate scandals, which has been documented in the relevant literature. As a result of the advances that have taken place, it has begun to be addressed by international organizations, governments, firms, and many organizations, all of which are looking for the most effective form of corporate governance in order to avoid scandals. The aim of thesis is to investigate recent corporate scandals and find out reasons led to them. The main research question of the study is “What are the causes of corporate scandals and how they can be avoided?”. Aim and question of thesis is tried to be solved through case study of Parmalat case. This investigation focuses on the phenomena of corporate scandal, including its impact and the factors that contributed to its emergence in other countries during the past several years. In order to contribute to the identification of the processes that led to the scandal in some institutions, a real scandal examples were examined. In addition, other major scandals and foreign publications on corporate governance were scanned, and important findings from regulatory institutions were used.
This was done in order to contribute to the identification of the processes that led to the scandal in some institutions. My diploma thesis is split up into three chapters. The first chapter provides an explanation of the concept of corporate governance as well as its guiding principles. The second chapter elaborates on the argument made in the first chapter and sets the tone for the subsequent study by describing significant characteristics of the recent spike in corporate scandals. In the last chapter, a case study of one of the most prominent corporate scandals that has ever occurred is presented which included Parmalat. There is a distinction to be made between the financial problems experienced by firms like Enron and Worldcom, which had differentiated ownership, and those experienced by corporations like Parmalat, which had concentrated ownership (management in a particular group). The top executives of Enron and Worldcom inflated the share price, the yield on the bond price, and the options that were owned by their companies through revenue manipulation and creative accounting practices. At Parmalat, members of the family stole money and property from the corporation.
Vedoucí práce: Vladimír Králíček
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: finance and accounting [obor dipl. práce]; diplomové práce; master's theses